Patrimonio Cultural Inmaterial y Oferta Turísticas en la Parroquia Licán, Cantón Riobamba - Morales Gaibor, Lady Yhajaira (2024)
ABSTRACT: The purpose of this study is to investigate “The Intangible Cultural Heritage and Tourist offer in the Licán parish, Riobamba canton.” Field research methods will be used to establish the relationship between knowledge use related to nature and the universe with the tourist offer of the parish. The immaterial cultural heritage of town is analyzed in order to promote its festivities. Documentary research in carried out with existing reviews, including bibliographic research within the cultural heritage, which leads us to disproportionately low progress in tourism. During a give period, we must collect information to describe each phenomenon and achieve the results as a method to organize surveys of the tourist population using an IBM SPSS version 23 program that was processed in the SPSS program system. In the end, after achieving the results, we moved on to the proposal of the safeguarding plan. We formulated a strategic philosophy approach, with the Foda matrix identifying the key points, to become a technical document on preserving, restoring, and protecting the cultural expressions within the parish of San Pedro de Licán.